Tumour lysis syndrome and acute kidney injury in high‐risk haematology patients in the rasburicase era. A prospective multicentre study from the Groupe de Recherche en Réanimation Respiratoire et Onco‐Hématologique. (15th June 2013) - Darmon, Michael; Vincent, François; Camous, Laurent; Canet, Emmanuel; Bonmati, Caroline; Braun, Thorsten; Caillot, Denis; Cornillon, Jérôme; Dimicoli, Sophie; Etienne, Anne; Galicier, Lionel; Garnier, Alice; et al.
Summary In tumour lysis syndrome (TLS), metabolic alterations caused by the destruction of malignant cells manifest as laboratory abnormalities with (clinical TLS) or without (laboratory TLS) organ dysfunction. This prospective multicentre cohort study included 153 consecutive patients with malignancies at high risk for TLS (median age 54 years (interquartile range, 38–66). Underlying malignancies were acute leukaemia (58%), aggressive non‐Hodgkin lymphoma (29.5%), and Burkitt leukaemia/lymphoma (12.5%). Laboratory TLS developed in 17 (11.1%) patients and clinical TLS with acute kidney injury (AKI) in 30 (19.6%) patients. After adjustment for confounders, admission phosphates level (odds ratio [OR] per mmol/l, 5.3; 95% confidence interval [95% CI], 1.5–18.3), lactic dehydrogenase (OR per x normal, 1.1; 95%CI, 1.005–1.25), and disseminated intravascular coagulation (OR, 4.1; 95%CI, 1.4–12.3) were associated with clinical TLS; and TLS was associated with day‐90 mortality (OR, 2.45; 95%CI, 1.09–5.50; P = 0.03). In this study, TLS occurred in 30.7% of high‐risk patients. One third of all patients experienced AKI, for which TLS was an independent risk factor. TLS was associated with increased mortality, indicating a need for interventional studies aimed at decreasing early TLS‐related deaths in this setting.